Maternal outcomes of conservative management and cesarean hysterectomy for placenta accreta spectrum disorders: a systematic review and meta-analysis - Siman Pan; Minmin Han; Tianlang Zhai; Yufei Han; Yihan Lu; Shiyun Huang; Qing Zuo; Ziyan Jiang; Zhiping Ge (BMC, 2024)
Abstract Background Cesarean hysterectomy as a traditional therapeutic maneuver for placenta accreta spectrum (PAS) has been associated with serious morbidity, conservative management has been used in many institutions to treat women with PAS. This systematic review aims to compare maternal outcomes according to conservative management or cesarean hysterectomy in women with placenta accreta spectrum disorders. Methods A systematic literature search was performed in MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Web of Science, and four Chinese databases (Chinese Biomedical Literature Database, China National Knowledge Infrastructure, Chinese Wanfang database and VIP database) to May 2024. Included studies were to be retrospective or prospective in design and compare and report relevant maternal outcomes according to conservative management (the placenta left partially or totally in situ) or cesarean hysterectomy in women with PAS. A risk ratio (RR) with 95% confidence interval (95% CI) was calculated for categorical outcomes and weighted mean difference (WMD) with 95% CI for continuous outcomes. The Newcastle-Ottawa Quality Assessment Scale was used to assess the observational studies. All analyses were performed using STATA version 18.0. Results Eight studies were included in the meta-analysis. Compared with cesarean hysterectomy, PAS women undergoing conservative management showed lower estimated blood loss [WMD − 1623.83; 95% CI: -2337.87, -909.79], required fewer units of packed red blood cells [WMD − 2.37; 95% CI: -3.70, -1.04] and units of fresh frozen plasma transfused [WMD − 0.40; 95% CI: -0.62, -0.19], needed a shorter mean operating time [WMD − 73.69; 95% CI: -90.52, -56.86], and presented decreased risks of bladder injury [RR 0.24; 95% CI: 0.11, 0.50], ICU admission [RR 0.24; 95% CI: 0.11, 0.52] and coagulopathy [RR 0.20; 95% CI: 0.06, 0.74], but increased risk for endometritis [RR 10.91; 95% CI: 1.36, 87.59] and readmission [RR 8.99; 95% CI: 4.00, 12.21]. The incidence of primary or delayed hysterectomy rate was 25% (95% CI: 19-32, I 2  = 40.88%) and the use of uterine arterial embolization rate was 78% (95% CI: 65-87, I 2  = 48.79%) in conservative management. Conclusion Conservative management could be an effective alternative to cesarean hysterectomy when women with PAS desire to preserve the uterus and are informed about the limitations of conservative management. Prospero ID CRD42023484578.